Análise integrada e estrutura da paisagem das áreas de proteção permanente e zona ripária do baixo do Rio Doce - Ramos, André Luís Demuner (2012)
This dissertation studied the dynamic analysis of the existing landscape Permanent Protection Areas (based on Federal Law 4.771/1965) and the Riparian Zone of the Main Channel of the Lower Rio Doce. The objective of the study of the same in view of the high degree of degradation suffered both during the process of appropriation of the landscape. Through a historical review on the concept of landscape to its use today was possible to construct a theoretical and methodological framework in which the proposed Integrated Geographic Analysis of Landscape Structure and provided the conditions for conducting scientific research and technical foundation for construction and manipulation of information. The use of methods and techniques of this research allowed to develop a methodology satisfactory to both spatialize Areas of Permanent Protection of the margins of the main channel of the Lower Rio Doce, and to define the boundary of the Riparian Zone of the Lower Rio Doce. The analysis of the dynamics of the landscape of the Lower Rio Doce focusing on the structure of the landscape, through the interpretation of classes of land use and occupation as patches, corridors and matrix, brought something new is related to the Permanent Protection Areas and Riparian Zones.